AN ANALYSIS OF FACTORS INFLUENCING THE DEVELOPMENT OF SOCIAL ENTERPRISES IN REPUBLIC OF SERBIA: Development of social enertprise in Serbia - Ivanovic Djukic, Maja; Petrović-Ranđelović, Marija; Talić, Miljana (The European Journal of Applied Economics, 2020)
The paper investigates the impact of different factors on the establishment and development of social enterprises (SPs). The aim of the paper was to identify the key stimulants and restrictions of development of SPs in the Republic of Serbia and to propose measures the application of which can increase their long-term sustainability. The paper is based on exploratory research using data covering 27 interviews with founders of social enterprises in Republic of Serbia. By applying the methods of regression analysis it was found that favorable financial resources (especially grants) are the key stimulants for the establishment of social enterprises, while the enthusiasm of managers of social enterprises has the greatest impact on their development. It was found also that legal regulations and the macroeconomic environment as well as difficulties in accessing the market are serious restrictions on the establishment of social enterprises, while lack of knowledge in the field of marketing and management limit the development of social enterprises in Republic of Serbia.
Keywords: Social enterprises, stimulants, restrictions, long-term sustainability.